CREATION OF NEW SHAPE THROUGH THE PROCESS OF LIGHT REFRACTION - Abrar Abd Hamid, Musafir
Interest in objects in water makes us aware of a process that occurs in the water, namely the process of light refraction. The process of refraction of light can produce new shapes naturally, even though the resulting shape is different from the original object. In addition to shape, light refraction can also produce some new color parts that are not present in the original object, this is the reason for creating new forms of the refraction process. The method used in the process of making this work is to conduct refraction experiments using a round aquarium and a tube so that it can change the original shape into a different new shape. Experiments carried out also play light from dark to light, so that the resulting shapes have different properties from one another. The shape of an object that has undergone light refraction will elongate and curve following the refractive plane used. The resulting new shape is transferred into a digital two-dimensional form by means of photography. The resulting shape is then painted onto the canvas in an imitative way. Thus, the resulting work is in the form of a circle and an equilateral square. The new visuals produced from the experimental process have an abstract character, because the new visuals only consist of formal elements. Even though in the process of painting using the imitative method, the final result obtained does not represent the original object anymore.